Emerging Therapies in Neurorehabilitation II - Pons, José L.; Raya, Rafael; González, José.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book reports on the latest technological and clinical advances in the field of neurorehabilitation. It is, however, much more than a conventional survey of the state-of-the-art in neurorehabilitation technologies and therapies. It was written on the basis of a week of lively discussions between PhD students and leading research experts during the Summer School on Neurorehabilitation (SSNR2014), held September 15-19 in Baiona, Spain. Its unconventional format makes it a perfect guide for all PhD students, researchers and professionals interested in gaining a multidisciplinary perspective on current and future neurorehabilitation scenarios.  The book addresses various aspects of neurorehabilitation research and practice, including a selection of common impairments affecting CNS function, such as stroke and spinal cord injury, as well as cutting-edge rehabilitation and diagnostics technologies, including robotics, neuroprosthetics, brain-machine interfaces and neuromodulation.
Challenges in Neurorehabilitation and Neural Engineering -- Rehabilitation Technologies Applications in Stroke and Traumatic Brain Injury Patients -- Rehabilitation Technologies for Spinal Injury -- Rehabilitation Technologies for Cerebral Palsy -- Neural and Musculoskeletal Modeling: its Role in Neurorehabilitation -- Spinal Cord plasticity and Neuromodulation After SCI.- BCI Applied to Neurorehabilitation -- Robot-Assisted Rehabilitation Therapy: Recovery Mechanisms and their Implications for Machine Design -- Motor Control and Learning Theories -- Muscle Synergies in Clinical Practice: Theoretical and Practical Implications -- Workshop on Transcutaneous Functional Electrical Stimulation -- Virtual Rehabilitation.
Keywords: Biomedical engineering; Neurosciences; Clinical psychology; Rehabilitation; Mentally ill -- Rehabilitation; User interfaces (Computer systems).; Human-computer interaction; Control engineering; Robotics; Automation; Biomedical Engineering and Bioengineering; Neuroscience; Rehabilitation Psychology; User Interfaces and Human Computer Interaction; Control, Robotics, Automation